Design of Automatic Transfer Switch on A Renewable Energy Hybrid Grid System at PT Lentera Bumi Nusantara - Muhammad Abdillah; Tri Mutia; Teguh Aryo Nugroho; Nita Indriani Pertiwi (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2022)
Currently, the transition between renewable energy sources and PLN sources at PT LBN is done manually by conducting scheduled monitoring. However, this method is less efficient and depends on the readiness of the operator. Therefore, in this Final Project, the design and construction of an Automatic Transfer Switch (ATS) on a renewable energy hybrid grid system at PT LBN is carried out where the source switching is based on the battery voltage value so as to shorten the source switching time while protecting the battery from undervoltage conditions. The main components used in the construction of this ATS system are contactors, relays, relay control circuits, ESP32, LCD 1604, and voltage divider circuits. The result of this final project is an ATS system that has a voltage sensor error of 0 - 1.187%. The monitoring of the ATS system was also successfully accessed from near and remotely in real time. The ATS that was built has a faster source switching time than the manual method, which is 21.6 ms - 40.1 ms.